2020
DOI: 10.1002/hep.31197
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Fructose and Uric Acid Through Aldose Reductase Contribute to Experimental and Human Alcoholic Liver Disease

Abstract: Background and Aims Alcohol‐associated liver disease (ALD) is a common chronic liver disease worldwide with high morbidity and mortality, and no Food and Drug Administration–approved therapies. Fructose (dietary or endogenous), its metabolite uric acid, and aldose reductase (AR, the only endogenous enzyme that produces fructose) are strongly associated with the development of nonalcoholic fatty liver disease. However, the role of AR or its metabolites in ALD remains understudied and was examined using human sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 39 publications
0
40
0
Order By: Relevance
“…The first novel observation of Wang et al 7 in their study using liver specimens from AH patients found that marked upregulation of AR corresponded with the elevation of AR metabolites (hepatic sorbitol, fructose and uric acid). More importantly, they observed a strong positive correlation between AR upregulation with AR metabolites and the endoplasmic reticulum (ER) stress markers activating transcription factor 3 (ATF3) and CCAAT/enhancer-binding protein homologous protein (CHOP), and a significant negative correlation with the protective chaperone proteins glucoseregulated protein (GRP)78 and GRP94 in the AH patients' livers.…”
mentioning
confidence: 95%
See 4 more Smart Citations
“…The first novel observation of Wang et al 7 in their study using liver specimens from AH patients found that marked upregulation of AR corresponded with the elevation of AR metabolites (hepatic sorbitol, fructose and uric acid). More importantly, they observed a strong positive correlation between AR upregulation with AR metabolites and the endoplasmic reticulum (ER) stress markers activating transcription factor 3 (ATF3) and CCAAT/enhancer-binding protein homologous protein (CHOP), and a significant negative correlation with the protective chaperone proteins glucoseregulated protein (GRP)78 and GRP94 in the AH patients' livers.…”
mentioning
confidence: 95%
“…In primary hepatocytes, either fructose or uric acid attenuated cell viability, and also markedly upregulated ATF3 and CHOP. It is interesting and valuable that AR upregulation was observed as a result of exposure to fructose or uric acid, indicating a kind of a feed-forward mechanism 7 . The observation of this mechanism induced by AR metabolites seems to be highly significant in consideration of a trigger for AR upregulation caused by alcohol.…”
mentioning
confidence: 99%
See 3 more Smart Citations